Proceedings IEEE International Conference on Application-Specific Systems, Architectures, and Processors. ASAP 2003
DOI: 10.1109/asap.2003.1212837
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable computing and electronic nanotechnology

Abstract: In this paper we examine the opportunities brought about by recent progress in electronic nanotechnologyMoore's law has been equated with a guaranteed stream of good news, bringing ever higher clock speeds and more hardware resources in each new hardware generation. Microarchitects have been significant beneficiaries, building faster processors and using more resources to exploit program parallelism. However, significant difficulties loom for the traditional approach to processor design.Traditional microarchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Moreover given the substantial degree of uncertainty inherent to nanoscale technologies, design will have to be framed in a probabilistic setting, if effective optimization of performance, yield, and other key figures of merit is to be achieved. It has been demonstrated that nanoelectronics technology is well suited to building reconfigurable computational fabrics [1,9,11]. This is significant because reconfigurability provides a powerful tool to circumvent the uncertainty associated with distributions of defects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover given the substantial degree of uncertainty inherent to nanoscale technologies, design will have to be framed in a probabilistic setting, if effective optimization of performance, yield, and other key figures of merit is to be achieved. It has been demonstrated that nanoelectronics technology is well suited to building reconfigurable computational fabrics [1,9,11]. This is significant because reconfigurability provides a powerful tool to circumvent the uncertainty associated with distributions of defects.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, an unstructured approach that requires mapping, synthesis and configuration at such a fine granularity would not scale for large nanosystems. In addition, the group testing strategy used for defect mapping in [9,11] requires unlimited connectivity among nanoblocks. Still, the key idea of using reconfiguration to achieve defect avoidance is the starting point for our work.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research in defect tolerance in the nanoelectronic systems includes system level approaches [8] and logic level solutions [9,10]. These approaches reconfigure the redundant hardware to bypass the permanent faulty units.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the fault masking The work of the first two authors is supported in part by NSF Grant 0082325. schemes, online repair schemes require significantly less hardware overhead [4], especially for regular systems where replacement of faulty components can be performed with common backup units [6,7]. In fact, as bottom-up fabrication, the expected mode of future nano circuit assembly, can only produce regular structures [8,9], a reconfiguration capability is necessary in any nanoelectronic system for the purpose of functionality formation in a post-fabrication stage, thus supporting repair online as well [10].…”
Section: Introductionmentioning
confidence: 99%